1984
DOI: 10.1079/pns19840051
|View full text |Cite
|
Sign up to set email alerts
|

The Nuffield Home Economics project

Abstract: Nuffield Home Economics is the first major curriculum development for pupils in the 13-16 age-range. The materials are designed to cover home economics education in two phases: a basic course for pupils up to the age of 14 years and a 2-year second-phase course to include the 16+ examination. The subject is divided into four areas of study: I. Food science. Food as a resource; the biological, chemical and physical nature of food; the principles of food handling; the methods of preparation and cooking and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…1 a–d). Directional strains were defined as follows: radial direction is normal to the mid-curve pointing outside the myocardium; circumferential direction runs along the circumference of the myocardium in the short axis plane, defined in such a way that the radial–longitudinal–circumferential coordinate system is right-handed; and longitudinal direction runs from the apex to the base [ 9 , 21 ]. Peak strains and displacements, taken as the maximum absolute value, for each direction and for each ventricle were measured in all subjects and mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 a–d). Directional strains were defined as follows: radial direction is normal to the mid-curve pointing outside the myocardium; circumferential direction runs along the circumference of the myocardium in the short axis plane, defined in such a way that the radial–longitudinal–circumferential coordinate system is right-handed; and longitudinal direction runs from the apex to the base [ 9 , 21 ]. Peak strains and displacements, taken as the maximum absolute value, for each direction and for each ventricle were measured in all subjects and mice.…”
Section: Methodsmentioning
confidence: 99%
“…demonstrated that in electrically isolated canine hearts, approximately 70% of RV pressure and pulmonary flow was generated during LV contraction alone [ 7 ] emphasizing the importance of proper LV function for normal RV function. A study on patients with a systemic-loaded RV demonstrated that LV mechanical dysfunction in ventricular strain and twisting had a significant effect on RV mechanics [ 8 ], and others have shown prognostic value in reduced LV and RV myocardial strain for prediction of adverse outcome in both adults [ 9 ] and children [ 10 ]. These studies are strongly indicative of the LV’s influence on RV function, yet they do not investigate altered ventricular mechanical interdependence longitudinally in PAH, nor explore potential therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%